Efektivitas Program Pemberian Makanan Tambahan pada Ibu Hamil Kekurangan Energi Kronik di Puskesmas Cikupa, Kabupaten Tangerang - Novianti, Anugrah; Utami, Tyas Putri; Kherunnisa, Rifka Dewi; Indriani, Nisa (Idea Pengabdian Masyarakat, 2022)
Nutritional problems that are often encountered in pregnant women include Chronic Energy Deficiency (CED). Chronic Energy Deficiency (CED) is a condition of a person who suffers from chronic (chronic) food shortages, which is characterized by an upper arm circumference (LILA) < 23.5 cm, resulting in health problems. The purpose of community service activities is to look at the effectiveness of the supplementary feeding program for pregnant women with SEZ for 3 weeks. According to the service team survey, the high number of pregnant women who are at high risk (experiencing anemia and CED) from 10 villages in the Cikupa District Health Center, namely around 247 pregnant women with SEZ and 494 pregnant women with anemia throughout 2021. The method of service is case study, persuasive and educative to the community. The results of the service showed that there was a difference in the weight of pregnant women (n=27) before and after the PMT intervention for 3 weeks, so that giving PMT was considered effective for increasing the weight of pregnant women with SEZ significantly.